Positive temperature coefficient of the thermal conductivity above room temperature in a perovskite cobaltite. Issue 1 (31st December 2022) - Doi, Atsunori; Shimano, Satoshi; Kriener, Markus; Kikkawa, Akiko; Taguchi, Yasujiro; Tokura, Yoshinori
ABSTRACT: The thermal conductivity above room temperature is investigated for LaCoO3 -based materials showing spin-state and insulator-metal crossovers. A positive temperature coefficient (PTC) of the thermal conductivity is observed during the insulator-metal crossover around 500 K. Our analysis indicates that the phononic thermal transport is also enhanced in addition to the electronic contribution as the insulator-metal crossover takes place. The enhancement of the phononic component is ascribed to the reduction of the incoherent local lattice distortion coupled with the spin/orbital state of each Co 3+ ion, which is induced by the enhanced spin-state fluctuation between low and excited spin-states. Moreover, fine tunability for the PTC of the thermal conductivity is demonstrated via doping hole-type carriers into LaCoO3 . The observed enhancement ratio of the thermal conductivity κ T (773 K) / κ T (323 K) = 2.6 in La0.95 Sr0.05 CoO3 is the largest value among oxide materials which exhibit a PTC of their thermal conductivity above room temperature. The thermal rectification ratio is estimated to reach 61% for a hypothetical thermal diode consisting of La0.95 Sr0.05 CoO3 and LaGaO3, the latter of which is a typical band insulator. These results indicate that utilizing spin-state and orbital degrees of freedom in strongly correlated materials is a useful strategy for tuning thermal transport properties, especially for designing thermal diodes. GRAPHICAL ABSTRACT: uf0001